A TRPV6 expression atlas for the mouse. (December 2021) - Wartenberg, Philipp; Lux, Femke; Busch, Kai; Fecher-Trost, Claudia; Flockerzi, Veit; Krasteva-Christ, Gabriela; Boehm, Ulrich; Weissgerber, Petra
Highlights: Identification of primary TRPV6 channel-expressing cells in an organism-wide manner. Additional characterization of TRPV6 expression in different tissues by immunoprecipitation (IP) followed by mass spectrometry analysis. Correlating mass spectrometry data with reporter gene expression. Establishment of a TRPV6 expression atlas throughout the entire body of juvenile and adult mice as a novel resource to investigate the physiological role of TRPV6 channels in vivo . Abstract: The transient receptor potential vanilloid 6 (TRPV6) channel is highly Ca 2+ -selective and has been implicated in mediating transcellular Ca 2+ transport and thus maintaining the Ca 2+ balance in the body. To characterize its physiological function(s), a detailed expression profile of the TRPV6 channel throughout the body is essential. Capitalizing on a recently established murine Trpv6 -reporter strain, we identified primary TRPV6 channel-expressing cells in an organism-wide manner. In a complementary experimental approach, we characterized TRPV6 expression in different tissues of wild-type mice by TRPV6 immunoprecipitation (IP) followed by mass spectrometry analysis and correlated these data with the reporter gene expression. Taken together, we present a TRPV6 expression atlas throughout the entire body of juvenile and adult mice, providing a novel resource to investigate the role of TRPV6 channels in vivo . Graphical abstract: Image, graphical abstract